Extracolonic findings on computed tomographic colonography in symptomatic patients: retrospective study. - Spirov, Vasilcho; Spirov, Goran (Macedonian Association of Physiologists and Anthropologists, 2017)
Computed tomographic colonography (CTC) represents a minimally invasive, safe and robust tool for evaluating colorectal lesions. CTC is well established in screening settings, and as well as in symptomatic patients as a colonoscopy alternative. The cross-sectional nature of CTC allows examining of colon and rectum and also extra colonic structures like abdominal parenchymal organs, vessels, bones, and soft tissue in the scanning range with low-dose. Thus extra colonic findings (ECFs) are also detected. Benefits are potentially life-saving in small percentage of patients. Most ECFs stay clinically insignificant. Intravenous administration (IV) of contrast medium increases the number of ECFs, but does not ultimately increase the number of clinically significant lesions. A system for categorization of ECFs is established, C-RADS, and most of them are classified as clinically unimportant prior further research. So, the effect of the detection of the ECFs remains controversial. Our aim was to analyze the incidence and the significance of ECFs in symptomatic adults, when colonoscopy is not an option. This retrospective review of the CTC studies is performed at the University Clinic of Radiology in Skopje, Macedonia, from January, 2011 to December, 2015. Patients are referred by gastroenterologist or abdominal surgeon because of change in bowel habit, abdominal pain, rectal bleeding, anemia and/or weight loss. Exclusion criteria include history of malignancy, abdominal surgery or positive findings of previous abdominal CT examination. Study includes 83 consecutive symptomatic patients, 47 women and 36 men, median age of 58.6 years. CTC technique used is standardized with prior bowel preparation using cathartic osmotic cleansing agent. Positive fecal tagging is not included. Intravenous spasmolytic is not administrated. The distension of the colon is achieved by controlled insufflation of room air. Scanning is performed on multidetector computed tomography scanner with 64 rows of detectors (Somaton Definition AS, Siemens) (0.6-mm collimation, 0.7-mm reconstruction interval, tube-current modulation - range, 30–200mA - and 120 kVp). Supine and prone acquisitions are obtained for all patients. Additional prone acquisition is obtained 70 seconds after intravenous application of iodine contrast. ECFs are defined as unsuspected and unrelated to the colon, excluding anatomic anomalies or variations. ECFs are classified into: (1) clinically important findings requiring urgent medical or surgical management, and (2) unimportant findings with little immediate clinical relevance or no clinical importance. Vascular calcifications, degenerative disease of the spine without significant spinal canal stenosis, enlarged prostate or punctiform parenchymal calcifications are omitted from both groups. Statistical analysis is done using the chi square test and the t test assessing the frequency of important ECFs according to patient age, sex, and colorectal findings. Out of total 83 patients ECFs are identified in 15 patients, (15/83, 18%). The total number of ECFs is 19 (2 patients had more than one). ECFs are detected in 6 males, (6/36, 16.6%) and 9 females, (9/47, 19.1%). There are no significant differences in the mean age and sex. Two patients have significant ECFs (2/83, 2.5%), abdominal aneurism and renal cell carcinoma. The rest of the ECFs are unimportant (17/19, 89.5%). The most common lesion is cortical renal cyst. The IV application of contrast detected ECFs in three patients, 3.6% (3/83), two hemangiomas and renal cell carcinoma. Additional ultrasound examination was required in 4 patients, 4.8% (4/83). There was no need for patient follow up. There were no complications of the CTC or the workup. A total of 12/83 (14.4%) patients had colorectal lesion greater than 6 mm, of whom 5/83 (6%) had a colorectal malignancy. The incidence of ECFs was identical in the subset of patients with or without positive CTC study. Specifically CTC with administration of IV contrast medium could help detect and differentiate more ECFs and as a result extra colic diseases could be detected in earlier phase, or unnecessary diagnostic testing could be reduced as well as nonessential surgery and unnecessary patient anxiety. Cost and risks of administering IV contrast medium is not to be neglected. Effort is to be made for introducing selective contrast administration. As designed, this study with objectively limited number of participants, affirms the findings of other reported studies. CTC ECFs are valuable in various manners and should not be ever neglected.
Keywords: extracolonic findings; CT colonography; CT abdomen; incidentalomas